Inactivation of a broad spectrum of viruses and parasites by photochemical treatment of plasma and platelets using amotosalen and ultraviolet A light. Issue 6 (24th April 2020) - Lanteri, Marion C.; Santa‐Maria, Felicia; Laughhunn, Andrew; Girard, Yvette A.; Picard‐Maureau, Marcus; Payrat, Jean‐Marc; Irsch, Johannes; Stassinopoulos, Adonis; Bringmann, Peter
Abstract : BACKGROUND: The INTERCEPT Blood System pathogen reduction technology (PRT), which uses amotosalen and ultraviolet A light treatment (amotosalen/UV‐PRT), inactivates pathogens in plasma and platelet components (PCs). This review summarizes data describing the inactivation efficacy of amotosalen/UVA‐PRT for a broad spectrum of viruses and parasites. METHODS: Twenty‐five enveloped viruses, six nonenveloped viruses (NEVs), and four parasites species were evaluated for sensitivity to amotosalen/UVA‐PRT. Pathogens were spiked into plasma and PC at high titers. Samples were collected before and after PRT and assessed for infectivity with cell cultures or animal models. Log reduction factors (LRFs) were defined as the difference in infectious titers before and after amotosalen/UV‐PRT. RESULTS: LRFs of ≥4.0 log were reported for 19 pathogens in plasma (range, ≥4.0 to ≥7.6), 28 pathogens in PC in platelet additive solution (PC‐PAS; ≥4.1‐≥7.8), and 14 pathogens in PC in 100% plasma (PC‐100%; (≥4.3‐>8.4). Twenty‐five enveloped viruses and two NEVs were sensitive to amotosalen/UV‐PRT; LRF ranged from >2.9 to ≥7.6 in plasma, 2.4 or greater to greater than 6.9 in PC‐PAS and >3.5 to >6.5 in PC‐100%. Infectious titers for four parasites were reduced by >4.0 log in all PC and plasma (≥4.9 to >8.4). CONCLUSION: Amotosalen/UVA‐PRT demonstrated effective infectious titer reduction for a broad spectrum of viruses and parasites. This confirms the capacity of this system to reduce the risk of viral and parasitic transfusion‐transmitted infections by plasma and PCs in various geographies.